Review of Studies on the Hot Spot Temperature of Oil-Immersed Transformers - Lin, Lin; Qiang, Chengdan; Zhang, Hui; Chen, Qingguo; An, Zhen; Xu, Weijie (Energies (Basel), 2025)
Oil-immersed transformers are the core equipment of power systems for energy transfer. The thermal characteristic of a transformer immediately affects its operational reliability and service life. Therefore, analyzing the hot spot temperature of transformers is highly important. Currently, researchers worldwide have achieved substantial research results in this field. This paper reviews the research status of the transformer hot spot temperature. First, the calculation method of transformer loss, the forms of heat transfer and its calculation method, the characteristics of the cooling method, and its application occasions are summarized. Second, the methods used to research the transformer hot spot temperature are presented in detail. From the perspective of transformer heat production and heat dissipation, research results on the factors influencing transformer hot spot temperature are summarized. Last, the research direction of the transformer hot spot temperature is indicated.